2008
DOI: 10.1097/bpo.0b013e318164fa79
|View full text |Cite
|
Sign up to set email alerts
|

Friedreich's Ataxia and Scoliosis

Abstract: Patients with Friedreich's ataxia need to be carefully screened for scoliosis and counseled about the high rate of surgical fusion. Using modern implants, correction can be achieved and maintained.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(16 citation statements)
references
References 12 publications
0
16
0
Order By: Relevance
“…This disorder is caused by an expansion repeat of the GAA trinucleotide on the 9q13 chromosome, leading to iron deposition in the mitochondria and ultimately creation of free radicals [ 35 ]. Cardiomyopathy leads to death in many patients before the age of 40 [ 36 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This disorder is caused by an expansion repeat of the GAA trinucleotide on the 9q13 chromosome, leading to iron deposition in the mitochondria and ultimately creation of free radicals [ 35 ]. Cardiomyopathy leads to death in many patients before the age of 40 [ 36 ].…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, they concluded that there was no significant impact from surgical correction on what age patients became wheelchair bound. Despite cardiomyopathy concerns, the authors felt that surgery could be preformed safely with close anesthesia monitoring [ 36 ].…”
Section: Resultsmentioning
confidence: 99%
“…2022 In one study, 20% of individuals with Friedreich ataxia required the prescription of a brace and 33% required spinal fusion. 21 Pes cavus is common, occurring in 55% to 75% of individuals with Friedreich ataxia (Table 3), but it rarely causes morbidity. Equinovarus deformity of the feet is more commonly a cause of morbidity.…”
Section: Friedreich Ataxia Due To Homozygous Fxn Intron 1 Gaa Expansionsmentioning
confidence: 99%
“…Most people diagnosed with the disorder require mobility aids such as a cane, walker or wheelchair by their teens or early 20s, and may require surgery for scoliosis or foot deformities [6]. Regular follow-up with annual echocardiograms and blood tests are necessary to detect and monitor the development of cardiac involvement and diabetes.…”
Section: Introductionmentioning
confidence: 99%